International water transfer and sharing: The case of the Ganges River - Bhaduri, Anik; Barbier, Bruno (Cambridge University Press, 2008)
The following paper is concerned with water sharing of the Ganges River between India and Bangladesh, with possible augmentation through water transfers from Nepal. We analyzed the case when water from Nepal can be transferred to Bangladesh through the upstream country, India, as the local geography only permits such water transfer. A game theoretic model is formulated to determine the optimal share of water diverted to Bangladesh by India, and the optimal amount of water transfer from Nepal. India may gain positive externalities from such water transfer. The positive externalities generated from water transfer from Nepal may influence the water share of both India and Bangladesh. In the absence of altruism, India would allow less water flow to Bangladesh than in the case when there is no provision to buy water from Nepal. We also explored whether positive externalities could induce India to buy water jointly with Bangladesh, and such a case will only occur if the countries possess altruistic concerns and share water according to an agreement.